PERAN MEDIA SOSIAL DALAM MENINGKATKAN PEMAHAMAN AGAMA ISLAM DI KALANGAN GENERASI MILENIAL - Rida Faizah; Maftuhah maf tuhah (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
The advancement of technology and the development of social media have opened new opportunities for the dissemination of Islamic religious information, especially for millennials who are actively using digital platforms. This study aims to explore the role of social media in enhancing the understanding of Islam among millennials. Using a qualitative approach with a literature review method, this research examines various social media platforms such as Instagram, YouTube, and TikTok that provide religious content, as well as their impact on millennials' understanding, practices, and religious identity. The findings indicate that social media significantly enhances religious knowledge by providing content that is engaging, interactive, and easily accessible, thus reaching millennials who prefer concise and visual content. Additionally, social media contributes to fostering a moderate religious identity through the dissemination of Islamic values that promote tolerance and inclusivity. However, a major challenge identified is the risk of spreading invalid religious information and the emergence of extreme interpretations that may lead to biased religious understanding. This study emphasizes that social media plays an essential role as a medium for religious education if managed wisely, supervised appropriately, and complemented with digital literacy. Thus, social media is not only an effective tool for religious outreach but also a strategic instrument in supporting the reinforcement of moderate Islamic understanding among millennials.